PENGARUH PENGGUNAAN LITERASI BACA TULIS TERHADAP KEMAMPUAN MEMBACA SISWA KELAS VII MTS AZ-ZIKRA KOTA SORONG - Olive Marisa Mirachel Kambuaya; Abdulrahman Hatsama; Siti Fatihaturahmah Al Jumroh (Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study aims to determine the effect of reading and writing literacy on the reading ability of seventh-grade students at MTs Az-Zikra Sorong City. Reading and writing literacy is considered an essential foundation for learning success as it relates to the ability to understand information, process ideas, and re-express them in oral and written forms. The method used in this research was quantitative with a descriptive approach. Data were obtained through questionnaires and reading ability tests involving twenty students as research respondents. The analysis was conducted by comparing the results of the pre-test and post-test after the implementation of literacy-based learning activities. The findings indicate an increase in the average score of students’ reading ability from a moderate to a better category after the treatment was applied. Students became more capable of identifying main ideas, understanding vocabulary, and drawing conclusions from texts. These findings prove that the habituation of reading and writing literacy has a positive contribution to the development of reading skills. Therefore, literacy programs need to be implemented continuously and integrated into the learning process at school.